2018
DOI: 10.1553/giscience2018_01_s162
|View full text |Cite
|
Sign up to set email alerts
|

Considering Spatial Factors in Promoting Active, Healthy Commuting

Abstract: Although mobility is spatial by its very nature, spatial factors are rarely explicitly considered in the promotion of active commuting. However, active commuting bears great potential for increasing physical activity among employees and can thus contribute to health promotion. We argue that spatial models and analyses are building blocks for more efficient strategies in corporate mobility and health promotion measures. Specifically, we propose (a) a routing algorithm that optimizes commuting journeys in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Studies have also revealed that there are certain strategies like walking home from work rather than to work when time pressure exists 40 . But still, very few studies 16,41 have objectively measured the contribution of walking to work to physical activity levels and increase in physical performance, so that more evidence is still needed 42 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also revealed that there are certain strategies like walking home from work rather than to work when time pressure exists 40 . But still, very few studies 16,41 have objectively measured the contribution of walking to work to physical activity levels and increase in physical performance, so that more evidence is still needed 42 …”
Section: Discussionmentioning
confidence: 99%
“…Also Giles‐Corti et al 40 as well as Sallis et al 41 called for better planning of cities to make active transportation but also physical activity, in general, more attractive. Adequate infrastructure is fundamental for physically active commuting 42 . On the other hand, one might argue that it is impossible for many employees to commute actively, as distances are too long.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results as well as on other studies, 32,43 active commuting may be recommended to policymakers, employers, employees, co‐workers, or patients in order to improve physical activity and exercise capacity and to possibly even reduce mortality in the working force. On the one hand, much needs to be done with respect to infrastructure to make active commuting more attractive, as adequate infrastructure is fundamental for active commuting 42 . Only then an increasing number of employees can benefit from its health effects.…”
Section: Perspectivesmentioning
confidence: 99%
“…The modelling of raster-based strengths and weaknesses for promoting active and sustainable mobility is built on the output datasets from the GISMO project (Loidl et al, 2018). In these datasets, PT quality, and the walkability and bikeability of a location (100-metre cell) are rated with different indices.…”
Section: Modelling Strengths and Weaknesses For Active And Sustainabl...mentioning
confidence: 99%